SCAFFOLDING STRATEGY IN IMPROVING STUDENTS' READING COMPREHENSION : A quasi-experimental research in eight grade students of one junior high school in bandung - Gita, Nurfalah (2017)
The study entitled "Scaffolding Strategy in Improving Students' Reading Comprehension" was carried out to investigate the effectiveness of scaffolding strategy in improving students' reading comprehension and the students' responses toward the treatment. In this study, two different treatments were given to be compared. Therefore, the quasi-experimental method was conducted. As the participants of the research, two classes were taken, namely experimental group and control group. Thus, pre-test and post-test were administered as the procedure of quasi-experimental method to obtain the data. This study employed a questionnaire as the instrument of the research to obtain the data. The result of the data indicated that scaffolding strategy was able to reveal statically significant result toward students' reading comprehension. Moreover, the students' responses which were collected through the questionnaire mostly revealed positive attitudes. Therefore, the implementation of scaffolding strategy is effective especially in improving students' reading comprehension.